2016
DOI: 10.1111/1365-2664.12644
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of climate change and disturbance on spatio‐temporal trajectories of biodiversity in a temperate forest landscape

Abstract: Summary1. The ongoing changes to climate challenge the conservation of forest biodiversity. Yet, in thermally limited systems, such as temperate forests, not all species groups might be affected negatively. Furthermore, simultaneous changes in the disturbance regime have the potential to mitigate climate-related impacts on forest species. Here, we (i) investigated the potential long-term effect of climate change on biodiversity in a mountain forest landscape, (ii) assessed the effects of different disturbance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
144
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 155 publications
(154 citation statements)
references
References 49 publications
8
144
2
Order By: Relevance
“…The direction of the effect of climate change can vary from positive to negative and it is often difficult to disentangle indirect and direct effects, as well as tri-trophic interactions. Predictions based on the link between climate change and insect disturbances are important, as insects are critical to forest succession [5,149]. Modeling is a useful tool, although predictions can be misleading when input data are scarce or not appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…The direction of the effect of climate change can vary from positive to negative and it is often difficult to disentangle indirect and direct effects, as well as tri-trophic interactions. Predictions based on the link between climate change and insect disturbances are important, as insects are critical to forest succession [5,149]. Modeling is a useful tool, although predictions can be misleading when input data are scarce or not appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…, Thom et al. ). For the specific context of the current study area, we successfully evaluated the model's capability to reproduce observed tree productivity, sensitivity to interannual climate variation, and potential natural vegetation composition at the landscape scale (see Thom et al.…”
Section: Methodsmentioning
confidence: 99%
“…iLand has been successfully applied and evaluated for temperate forest landscapes in North America (Seidl et al 2012a(Seidl et al , b, 2014b, and Europe (Seidl et al 2014a, Thom et al 2017c, L. Dobor, T. Hl asny, W. Rammer, I. Barka, J. Trombik, P. Pavlenda, V.…”
Section: Simulation Modelmentioning
confidence: 99%